Profil buku "Lihat Sekitar" kelas IV ditinjau dari Representasi kecerdasan verbal linguistik dan logis matematis - Monica Rini Widiastuti; Karsono Karsono; Siti Kamsiyati (Didaktika Dwija Indria, 2023)
Textbooks are elements of the curriculum that function as learning resources for students, while for teachers, textbooks function to assist the implementation of learning. The purpose of this research is to identify and explain verbal-linguistic intelligence and logical-mathematical intelligence in student textbooks for grade IV Bahasa Indonesia Kurikulum Merdeka. This research is qualitative research using literature study, document study, and note-taking techniques. The validity of the data obtained was tested through source triangulation in the form of a teacher's handbook and through increased persistence. The data obtained were then analysed using the Miles and Huberman interactive model. The results of the study are presented in tabular form and described using descriptions to show representations of verbal-linguistic intelligence and logical-mathematical intelligence. The results showed that writing skills were dominantly developed in activities in students' textbooks while listening skills were still low. Meanwhile, student activity in textbooks shows a dominant representation of verbal-linguistic intelligence compared to logical-mathematical intelligence.